Sephardiellinae, a new Middle Triassic conodont subfamily - Plasencia, P.; Márquez- Aliaga, A.; Hirsch, F. (Journal of Iberian Geology, 2007)
Sephardiellinae (nov. subfam.) encompasses a Middle Triassic Gondolleloid lineage that originated in the Sephardic realm, westernmost shallow Neotethys, from where, in the course of the Ladinian and earliest Carnian, some of its species spread to the world oceans, before extinction as a result of the Carnian salinity crisis. It is composed of two genera, Sephardiella and Pseudofurnishius. Differential criteria in its septimembrate apparatus are the basal cavity structure of P1 element and morphological variations in the P2 and S3 elements.